Cykliczność zmian struktury nakładów inwestycyjnych w makroregionie środkowo-zachodnim - Małuszyńska, Ewa (Wydział Prawa i Administracji UAM, 1992)
Regional cycles are a relatively r a r e topic in t h e literature on spatial problems. The observation of changes occurring at a regional level have led the author to the supposition that regional development may be characterized by a cyclical variability. The outcome of research presented in the article confirmed in principle the hypotheses formulated by the author.
Cyclical variability of changes of a investment outlays structure and, employment in Mid-Western Macroregion